A new possibility in fertility preservation: The artificial ovary. (10th July 2019) - Cho, Eun; Kim, Yoon Young; Noh, Kevin; Ku, Seung‐Yup
Abstract: Conventional fertility preservation methods such as oocyte or embryo cryopreservation are currently insufficient to treat including those patients with prepubertal cancer and premature ovarian failure. Ovarian tissue cryopreservation presents as an alternative but has limitations with a potential risk of reintroducing malignant cells in patients who recover from cancer, those of chemotherapy prior to tissue cryopreservation. The so called "artificial ovary" aims to resolve this issue by transplanting isolated follicles with or without a biological scaffold. The artificial ovary may also offer an effective alternative option for those who cannot benefit from traditional assisted reproductive techniques such as in vitro fertilisation. To date, in animal studies and human trial, the artificial ovary restored endocrine function, achieved in vivo follicular development, and resulted in successful pregnancies. However, development of a technique for higher follicular recovery rate and a more optimised design of delivery scaffold, better transplantation techniques to prevent postsurgical ischemia, and consideration for genetic safety are required for safer and consistent human clinical applications. Ideas from different transplantation surgeries (e.g., entire ovary, ovarian cortex, and transplantation with tissue‐engineered products) can be applied to enhance the efficacy of artificial ovarian transplantation. For the better application of artificial ovary, a deeper understanding of mechanical and biochemical properties of the ovary and folliculogenesis after cryopreservation, transplantation with or without scaffold, and development of sophisticated in vivo imaging techniques of transplanted artificial ovary need to precede its efficient clinical application.